2020
DOI: 10.3389/fimmu.2020.569988
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Immunization With Nucleotide Enzymes of Schistosoma mansoni: Nucleoside Diphosphate Kinase and Adenylosuccinate Lyase as New Antigenic Targets Against Schistosomiasis

Abstract: Immunization With Schistosoma mansoni Proteins groups there were reductions in egg counts in the liver and intestine, such as reductions in liver granulomas. Thus, we suggest that immunizations with these enzymes could contribute to the reduction of schistosomiasis transmission, besides being important in immunopathogenesis control of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…The images of histological sections showed that the fibrosis process is more accentuated in animals that were treated with the HGPRT enzyme, as the eggs were more likely to be destroyed and the fibrous process was also accentuated, showing that HGPRT can positively interfere in the physiopathology process of schistosomiasis that severely affects the liver. The same response profile was observed in the study that tested the enzymes NDPK, ADSL and MIX in mice as immunizing agents, showing that the purine salvage pathway enzymes of S. mansoni interfere with the reduction of liver fibrosis [17].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The images of histological sections showed that the fibrosis process is more accentuated in animals that were treated with the HGPRT enzyme, as the eggs were more likely to be destroyed and the fibrous process was also accentuated, showing that HGPRT can positively interfere in the physiopathology process of schistosomiasis that severely affects the liver. The same response profile was observed in the study that tested the enzymes NDPK, ADSL and MIX in mice as immunizing agents, showing that the purine salvage pathway enzymes of S. mansoni interfere with the reduction of liver fibrosis [17].…”
Section: Discussionsupporting
confidence: 74%
“…The value obtained in the present study on the reduction of the parasite load (30.06% in the Sm + HGPRT group in Swiss mice) is superior to the value obtained for the decrease from 16.21% to 25% in the values of the parasite load after a recombinant insoluble protein that is expressed in the gastrodermis and integument of adult S. mansoni worms as a kind of vaccination [27]. In studies with the NDPK and HGPRT enzymes from the S. mansoni rescue route used in immunization in mice infected with S. mansoni, it was showed a slight reduction in the number of worms [16,17]. The decrease in the burden of worms after teraphy with HGPRT therapy is remarkably similar to the levels attained in additional tests using others enzymes in the immunization of mice, where worm recovery was between the 45th and the 50th day following infection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations